Hallmarks of crustacean immune hemocytes at single-cell resolution - Xin, Fan; Zhang, Xiaobo (Frontiers in Immunology, 2023)
In invertebrates, hemocytes are the key factors in innate immunity. However, the types of invertebrate immune hemocytes are unclassified due to the limitation of morphological classification. To determine the immune hemocytes of crustaceans, the heterogeneity of hemocytes of shrimp Marsupenaeus japonicus and crayfish Procambarus clarkii, two representative crustacean species, were characterized in this study. The results of single-cell RNA sequencing indicated that shrimp and crayfish contained 11 and 12 types of hemocytes, respectively. Each of different types of hemocytes specifically expressed the potential marker genes. Based on the responses of shrimp and crayfish to the infection of white spot syndrome virus (WSSV) and the challenge of lipopolysaccharide (LPS), four types of immune hemocytes of crustaceans were classified, including semi-granular hemocytes involved in antimicrobial peptide production, granular hemocytes responsible for the production of antimicrobial peptides, hemocytes related to cell proliferation and hemocytes in immunity-activated state. Therefore, our study provided the first classification of crustacean hemocytes as well as of immune hemocytes of crustaceans at the single-cell resolution, which would be helpful to understand the innate immunity of invertebrates.